A systematic review of customer Sharia compliance behaviour in Islamic banks: Determinants and behavioural intention - Roni, Andespa; Yulia Hendri, Yeni; Fernando, Yudi; Dessy Kurnia, Sari (Emerald Publisher, 2024)
Purpose: This study aims to investigate what past scholars have learned about Muslim consumer compliance behaviour in Islamic banks and identify what future research is needed. In addition, it also explores the relationship model between the previously studied determining factors and the customer’s Sharia compliance behaviour. Design/methodology/approach; This study used a bibliometric–systematic literature review analysis using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) technique by reviewing the articles published from 2013 to 2023. The PRISMA procedures involved several stages, including identification, screening, eligibility, analysis and conclusion based on the findings. Findings: The results found that customer Sharia compliance behaviour determinants in Islamic banks are attitude, subjective norms, perceived behavioural control, Islamic financial literacy, religiosity, consumer conformity, Islamic branding and behavioural intention. Interestingly, the results indicated that such factors as consumer conformity, Islamic branding and sustainable intentions are less discussed. Practical implications: Decision-makers in Islamic banks must use digital technology to offer better service and make operations more reachable for customers to access information, complete transactions and manage their accounts by Sharia principles. Therefore, the bank needs to continually produce innovative products and services so that customers have a greater variety of options to suit their Sharia-compliant financial needs. Theoretically, this study has contributed by finding the main critical domains influencing customers’ Sharia compliance behaviour, such as attitudes, subjective norms, perceptions of behavioural control, knowledge of Islamic finance, religiosity, consumer conformity, Islamic branding and behavioural intentions. Then, it makes a theoretical contribution by establishing a model that explains how customers make decisions based on Sharia-related factors in the context of their purchases. Originality/value: Past studies focused on the Sharia compliance behaviour in paying Zakat for takaful customers. Therefore, this study provides critical factors of Sharia compliance behaviour on conformity, Islamic branding and sustainable intention regarding unexplored consensus on the determinants and outcomes of customer Sharia compliance behaviour of Islamic banking.